Successful Long-Distance Breeding Range Expansion of a Top Marine Predator - Henry, Robert William; Shaffer, Scott A.; Antolos, Michelle; Félix-Lizárraga, María; Foley, David G.; Hazen, Elliott L.; Tremblay, Yann; Costa, Daniel P.; Tershy, Bernie R.; Croll, Donald A. (Frontiers in Ecology and Evolution, 2021)
Little is known about the effects of large-scale breeding range expansions on the ecology of top marine predators. We examined the effects of a recent range expansion on the breeding and foraging ecology of Laysan albatrosses (Phoebastria immutabilis). Laysan albatrosses expanded from historical breeding colonies in the Central Pacific Ocean to the Eastern Pacific Ocean around central Baja California, Mexico, leading to a 4000 km shift from colonies located adjacent to the productive transition zone in the Central Pacific to colonies embedded within the eastern boundary current upwelling system of the Eastern Pacific California Current. We use electronic tagging and remote sensing data to examine the consequences of this range expansion on at-sea distribution, habitat use, foraging habitat characteristics, and foraging behavior at sea by comparing birds from historic and nacent colonies. We found the expansion resulted in distinct at-sea segregation and differential access to novel oceanographic habitats. Birds from the new Eastern Pacific colony on Guadalupe Island, MX have reduced ranges, foraging trip lengths and durations, and spend more time on the water compare to birds breeding in the Central Pacific on Tern Island, USA. Impacts of the range expansion to the post-breeding season were less pronounced where birds maintained some at-sea segregation but utilized similar habitat and environmental variables. These differences have likely benefited the Eastern Pacific colony which has significantly greater reproductive output and population growth rates. Laysan albatrosses have the plasticity to adapt to distinctly different oceanographic habitats and also provide insight on the potential consequences of range shifts to marine organisms.